The Role of Experiential Learning For Generation Z To Increase Students’ Understanding And Interest In The Auditor Profession - Santoso, Haychel Alexander; Sugiarti, Yenny (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Generation Z is known as a technology-literate generation, making access to learning easier to obtain and digest. This convenience through technology apparently still needs to be supported by appropriate learning methods, because Generation Z prefers practical rather than theoretical learning. Generation Z tends to learn based on the concept of learning by doing, which requires real practice and one of them is through experiential learning. The aim of this research is to explain the role of experiential learning, especially for Generation Z, to increase understanding of the auditor profession and increase their interest to become auditor. The experiential learning in question is an internship as an auditor. This research is qualitative research. Researchers conducted interviews with ten 7th semester student speakers who were undergoing internships at public accounting firms to explore their views on practical learning. The results show that after undergoing an internship as experiential learning, there is a significant increase in understanding of the duties and responsibilities of an auditor. Most of the interviewees plan to continue their careers as auditors when they graduate from college.